2010
DOI: 10.1103/physrevd.82.096011
|View full text |Cite
|
Sign up to set email alerts
|

Confinement in Maxwell-Chern-Simons planar quantum electrodynamics and the1/Napproximation

Abstract: We study the analytical structure of the fermion propagator in planar quantum electrodynamics coupled to a Chern-Simons term within a four-component spinor formalism. The dynamical generation of parity-preserving and parity-violating fermion mass terms is considered, through the solution of the corresponding Schwinger-Dyson equation for the fermion propagator at leading order of the 1/N approximation in Landau gauge. The theory undergoes a first order phase transition toward chiral symmetry restoration when th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Part of this rich physics stems from the existence of a Chern-Simons term. In three-dimensional QED (QED 3 ) the interplay of a Chern-Simons term and fermionic symmetry breaking was investigated in [18][19][20][21][22][23][24]. A consensus from these studies is that dynamical symmetry breaking is generally suppressed by a Chern-Simons term, because photons acquire a gauge-invariant mass term which in turn quenches quantum fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Part of this rich physics stems from the existence of a Chern-Simons term. In three-dimensional QED (QED 3 ) the interplay of a Chern-Simons term and fermionic symmetry breaking was investigated in [18][19][20][21][22][23][24]. A consensus from these studies is that dynamical symmetry breaking is generally suppressed by a Chern-Simons term, because photons acquire a gauge-invariant mass term which in turn quenches quantum fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the authors of Refs. [2,16] pointed out that restoration of chiral symmetry and deconfinement are coincident owing to an abrupt change in the analytic properties of the fermion propagator when a nonzero scalar self-energy becomes insupportable.…”
Section: Introductionmentioning
confidence: 99%
“…Inserting the above results into the decompositions ( 17) and (15), we obtain the one-loop correction to the fermion propagator, in accordance with Eq. ( 27) of Ref.…”
mentioning
confidence: 82%
“…Within the twocomponent fermion formalism, it was observed that while chiral symmetry can be broken, parity symmetry remains untouched [14]. Moreover, this term induces a detaching of chiral symmetry breaking-restoration and confinement-deconfinement transitions [15], leading to a phase resembling quarkonia, where chiral symmetry is restored, but confinement takes place [16]. Confinement and screening effects have been studied in this theory [17] through the behavior of the vacuum polarization.…”
Section: Introductionmentioning
confidence: 99%